2018
DOI: 10.1177/1479972317752763
|View full text |Cite
|
Sign up to set email alerts
|

Frailty: A global measure of the multisystem impact of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a multisystem disease that resembles the accumulation of multiple impairments seen in aging. A comprehensive geriatric assessment (CGA) captures multisystem deficits, from which a frailty index (FI) can be derived. We hypothesized that patients with COPD would be frailer than a comparator group free from respiratory disease. In this cross-sectional analysis, the CGA questionnaire was completed and used to derive an FI in 520 patients diagnosed with COPD and 150 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
5
46
0
Order By: Relevance
“…Median HGS was significantly different between the low, medium, and high EuroSCORE operative risk scores (20 positive correlations between the BIA body composition parameters fat-free mass (FFM), body cell mass (BCM), and fat mass (FM) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median HGS was significantly different between the low, medium, and high EuroSCORE operative risk scores (20 positive correlations between the BIA body composition parameters fat-free mass (FFM), body cell mass (BCM), and fat mass (FM) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…14,18 HGS is strongly recommended, since it is a simple, quick, inexpensive, noninvasive, and easily accessible method. This highly sensitive test allows for early detection of strength loss and protein depletion and is a useful method for nutrition diagnosis and monitoring, 15,17,18 with broader applicability as a component in the determination of frailty 14,20,21 and as a prognostic index 22,23 for several clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that the differences between the prevalence reported in Maddocks’ study and our study were due to the physical or social characteristics of the two patient populations. On the other hand, a previous study also found a higher prevalence of frailty [ 11 , 29 ], but this result is not directly comparable because they used another framework or model of frailty. Moreover, Park’s study [ 11 ] should be considered with caution because patients were included based on COPD symptoms and not on the results of a post-bronchodilator spirometry, as recommended by the GOLD guidelines.…”
Section: Discussionmentioning
confidence: 58%
“…Not surprisingly, many of these persons had some functional disability. Patients with COPD are more likely to be frail than other patients (8). A meta-analysis found that patients with COPD were twice as likely to be frail (9).…”
mentioning
confidence: 99%